Noninvasive Investigations for the Early Detection of Chronic Airways Dysfunction Following Lung Transplantation - Richard C Cook; Guy Fradet; Nestor L Muller; Daniel F Worsley; David Ostrow; Robert D Levy (Canadian Respiratory Journal)
BACKGROUND: The diagnosis of chronic rejection after lung transplantation is limited by the lack of a reliable test to detect airways disease early.